Awareness on cyber-bullying among high-school students, teachers, and parents - Tran, Van Cong (Đại học Quốc gia Hà Nội, 2020)
Background : Cyber-bullying has become an important issue in school. It can have negatives impacts on students'academic performance and mental health. Objective : This study aims to explore the awareness of students, teachers, and parents about cyber-bullying. Methods : A survey on cyber-bullying awareness were conducted on 135 students, 37 teachers and 88 parents ina secondary school and a high school in Ha Tinh province. Results show that 67.2 % of students, 61.4 % of parents and 70.3 % of teachers have heard about cyberbullying. Cyberbullying is mostly recognized as overt behaviors than convert behaviors. While most of the students, teachers, and parents are well aware of characteristics, behavioral expression, consequences, appropriate coping strategies, interconnection among agencies and prevention, on the other hand, a significant number of participants are unaware of the appropriate coping strategies as well considered for future research and recommendations for prevention and awareness raising programs are discussed. scrious consequences of cyberbullying